Laparoscopic Cholecystectomy in a Patient with Previous Pneumonectomy: A Case Report and Discussion of Anaesthetic Considerations - Dash Faith Newington; Sanaa Ismail (Case Reports in Anesthesiology)
Increasing numbers of patients require cholecystectomy after previous pneumonectomy, but there are little data to guide anaesthetic management. A laparoscopic approach is associated with less postoperative respiratory compromise than open cholecystectomy but may be relatively contraindicated due to the undesirable effects of pneumoperitoneum on respiratory function. We describe the case of a 72-year-old patient who successfully underwent elective laparoscopic cholecystectomy 23 years after left pneumonectomy. An understanding of the combined physiological consequences of pneumonectomy and pneumoperitoneum facilitated the provision of safe and uneventful anaesthesia. We propose that laparoscopic cholecystectomy is feasible and safe to perform in patients with a single lung.